C4 photosynthetic machinery: insights from maize chloroplast proteomics - Zhao, Qi; Chen, Sixue; Dai, Shaojun (Frontiers in Plant Science, 2013)
C4 plants exhibit much higher CO2 assimilation rates than C3 plants under certain conditions. The specialized differentiation of mesophyll cell and bundle sheath cell type chloroplasts is unique to C4 plants and improves photosynthetic efficiency. Maize (Zea mays) is an important crop and model with C4 photosynthetic machinery. 2DE and high-throughput quantitative proteomics approaches (e.g., isobaric tags for relative and absolute quantitation and shotgun proteomics) have been employed to investigate maize chloroplast structure and function. These proteomics studies have provided valuable information on C4 chloroplast protein components, photosynthesis, and other metabolic mechanisms underlying chloroplast biogenesis, stromal, and membrane differentiation, as well as response to salinity, high/low temperature, and light stress. This review presents an overview of proteomics advances in maize chloroplast biology.